Reliability of variables in the kinematic analysis of spring hurdles - Salo, A.; Grimshaw, P. N.; Viitasalo, J. T. (Medicine & Science in Sports & Exercise, 1997)
The purpose of this study was to investigate the reliability of kinematic variables in spring hurdles and to find out how many trials are needed to achieve reliable data. Seven British National level athletes in sprint hurdles were videotaped and all eight trials of each athlete were digitized from two camera views to produce three dimensional coordinates. The reliability of 28 kinematic variables across eight trials ranged from 0.54 to 1.00 for females and from 0.00 to 0.99 for males. The number of trials needed to reach a certain reliability level was evaluated using Spearman-Brown prophecy formula, and in the worst case (horizontal velocity lost for males) 78 trials would be needed to reach 0.90 reliability. The results showed reasonably high reliability, and the values for the female trials were generally higher than the male trials. The relative height of the hurdles enforces a more demanding clearance for males that can lead to increased variation within the subjects and thus lowered reliability. Subsequently, the results indicate that often more than one trial is needed to provide accurate quantitative results of the technique.